Industrial applications of quantum dots - Nur Farha, Shaafi; Saifful Kamaluddin, Muzakir (Elsevier, 2022)
Practical strategies of utilizing typical semiconducting materials with size smaller than the exciton Bohr radius—known as quantum confined structures, including the quantum dots (QDs) are needed. Numerous techniques have been explored to fabricate devices that contain specific size of the QDs, theoretically would exhibit favorable effects to the performance of the devices. The QDs have been proven could be synthesized using various techniques. However, there was always a debate whether the unique optoelectronic properties of a quantum-confined structure (e.g., multiple exciton generation and discrete energy levels) could be maintained in different batches of QDs with different size distributions. It is peculiar that numerous reports have shown the ability to synthesized QDs, however a technique that could isolate a specific size of QDs efficiently and/or a method that could maintain the size of the freshly synthesized QDs without altering their unique optoelectronic properties are yet to be demonstrated.